THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN AND TOTAL ASSETS TURNOVER ON STOCK PRICES IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE IDX IN THE 2019-2023 PERIOD: THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN AND TOTAL ASSETS TURNOVER ON STOCK PRICES IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE IDX IN THE 2019-2023 PERIOD - Kurniawati, Santi; Zulkarnain, Iskandar (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The purpose of this study is to determine and analyze the partial effect of the Current Ratio on Stock Prices; to determine and analyze the partial effect of the Debt to Equity Ratio on Stock Prices; to determine and analyze the effect of the Net Profit Margin on Stock Prices; to determine and analyze the effect of the Total Asset Turnover on Stock Prices; and to determine and analyze the simultaneous effect of the Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Total Asset Turnover on Stock Prices. This study uses a quantitative approach. The population consists of all financial reports of Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sampling technique used is purposive sampling or judgment sampling. The analytical technique applied is multiple linear regression and panel data regression using Eviews 12 software. The results of this study indicate that the Current Ratio (CR) partially has no significant effect on Stock Prices. The Debt to Equity Ratio (DER) partially has a negative and significant effect on Stock Prices. The Net Profit Margin (NPM) partially has a positive and significant effect on Stock Prices. The Total Asset Turnover (TATO) partially has no significant effect on Stock Prices. However, simultaneously, CR, DER, NPM, and TATO together have a significant effect on Stock Prices.